Development of Portfolio Assessment Instruments Based on Scientific Literacy on the Archaebacteria and Eubacteria Concepts - Ikawati Ikawati; Iing Dwi Lestari; Dwi Ratnasari; Indah Juwita Sari (International Journal of Biology Education Towards Sustainable Development, 2022)
This research aimed to develop the portfolio assessment instruments based on scientific literacy on the concept of the archaebacteria and eubacteria and to know the feasibility of the product. The research method was used Research and Development with research design: problem pontential and data collection, design of product, product development. The result of this research is portfolio assessment instruments based on scientific literacy with content cognitive assessment, affective assessment, psychomotor assessment, lesson plan, portfolio assessment, and presentation product and was judged by expert judgment consist aspect: construction, validity, language, scientific literacy and completeness used expert assessment sheets. The data obtained was analyzed with qualitative and quantitative. Based on the results of the  portfolio assessment instruments based on scientific literacy on the concept of the archaebacteria and eubacteria obtained was 87,8% with category very good and feasible to use.